Association Between Processed Electroencephalogram-Based Objectively Measured Depth of Sedation and Cerebrovascular Response: A Systematic Scoping Overview of the Human and Animal Literature - Froese, Logan; Dian, Joshua; Gomez, Alwyn; Batson, Carleen; Sainbhi, Amanjyot Singh; Zeiler, Frederick A. (Frontiers in Neurology, 2021)
Background: Current understanding of the impact that sedative agents have on neurovascular coupling, cerebral blood flow (CBF) and cerebrovascular response remains uncertain. One confounding factor regarding the impact of sedative agents is the depth of sedation, which is often determined at the bedside using clinical examination scoring systems. Such systems do not objectively account for sedation depth at the neurovascular level. As the depth of sedation can impact CBF and cerebral metabolism, the need for objective assessments of sedation depth is key. This is particularly the case in traumatic brain injury (TBI), where emerging literature suggests that cerebrovascular dysfunction dominates the burden of physiological dysfunction. Processed electroencephalogram (EEG) entropy measures are one possible solution to objectively quantify depth of sedation. Such measures are widely employed within anesthesia and are easy to employ at the bedside. However, the association between such EEG measures and cerebrovascular response remains unclear. Thus, to improve our understanding of the relationship between objectively measured depth of sedation and cerebrovascular response, we performed a scoping review of the literature. Methods: A systematically conduced scoping review of the existing literature on objectively measured sedation depth and CBF/cerebrovascular response was performed, search multiple databases from inception to November 2020. All available literature was reviewed to assess the association between objective sedation depth (as measured through processed electroencephalogram (EEG)) and CBF/cerebral autoregulation. Results: A total of 13 articles, 12 on adult humans and 1 on animal models, were identified. Initiation of sedation was found to decrease processed EEG entropy and CBF/cerebrovascular response measures. However, after this initial drop in values there is a wide range of responses in CBF seen. There were limited statistically reproduceable associations between processed EEG and CBF/cerebrovascular response. The literature body remains heterogeneous in both pathological states studied and sedative agent utilized, limiting the strength of conclusions that can be made. Conclusions: Conclusions about sedation depth, neurovascular coupling, CBF and cerebrovascular response are limited. Much further work is required to outline the impact of sedation on neurovascular coupling.